2016
DOI: 10.1128/jvi.00114-16
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus (HEV) Genotype 3 Infection of Human Liver Chimeric Mice as a Model for Chronic HEV Infection

Abstract: Genotype 3 (gt3) hepatitis E virus (HEV) infections are emerging in Western countries. Immunosuppressed patients are at risk of chronic HEV infection and progressive liver damage, but no adequate model system currently mimics this disease course. Here we explore the possibilities of in vivo HEV studies in a human liver chimeric mouse model (uPA ؉/؉ Nod-SCID-IL2R␥ ؊/؊ ) next to the A549 cell culture system, using HEV RNA-positive EDTA-plasma, feces, or liver biopsy specimens from 8 immunocompromised patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 32 publications
2
81
0
1
Order By: Relevance
“…(33) Because sofosbuvir inhibits G3 HEV replication in vitro and has shown antiviral activity in a patient with hepatitis E, it was recently reported as a candidate anti-HEV drug. (34,35) However, other reports have suggested that the inhibition of HEV replication by sofosbuvir is limited. (36,37) In our present experiments, a high concentration of PSI-7977 had only a limiting inhibitory effect against the virus replication, suggesting that sofosbuvir is not likely to be useful for the treatment of hepatitis E caused by G5 HEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…(33) Because sofosbuvir inhibits G3 HEV replication in vitro and has shown antiviral activity in a patient with hepatitis E, it was recently reported as a candidate anti-HEV drug. (34,35) However, other reports have suggested that the inhibition of HEV replication by sofosbuvir is limited. (36,37) In our present experiments, a high concentration of PSI-7977 had only a limiting inhibitory effect against the virus replication, suggesting that sofosbuvir is not likely to be useful for the treatment of hepatitis E caused by G5 HEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Interestingly, these reports indicated greater success using genotype 1 strains as inoculants (in contrast to in vitro studies) and all achieved greater infection and viraemia rates in inoculated mice using faecally derived HEV virions, in comparison to serum or culture derived. Two studies examined the use of ribavirin in inoculated chimeric mice and demonstrated the treatment to be successful in reducing viraemia in therapeutics.…”
Section: The Molecular Biology Of Hepatitis E Virusmentioning
confidence: 96%
“…Moreover, the co-housing of an HEV-infected mouse with three naïve humanized mice led to successful HEV infection, demonstrating that HEV infection can be transmitted through the faecal oral route in humanized mice, direct physical contact or micro-injuries [115]. HEV-inoculated human liver chimeric mice were also shown to develop chronic HEV infection [116,117] and the treatment of HEV-infected humanised mice with ribavirin led to a statistically significant decrease in the level of HEV RNA in the serum and the faeces and in no more liver damage [115,116]. The human liver chimeric mouse model seems then to be a valuable tool to study the biology of chronic HEV infection and evaluate preclinical drugs.…”
Section: Animal Models Of Hevmentioning
confidence: 99%